Pharmacotherapeutic Approaches in Tobacco Cessation and its Challenges: A Review (Indian Journal of Forensic Medicine & Toxicology, 2020)
Tobacco use is a global menace and leading cause of cancers and death. Tobacco cessation strategies arebeing formulated world over to curb this problem. Nicotine replacement therapy (NRT) such as chewinggum, patches and inhaler and drugs like Bupropion have shown some success in smoking cessation rates inthe short and long terms
Keywords: Tobacco cessation, Pharmacotherapy, NRT, Nicotine, Nicotine Patch, Bupropion.